2022
DOI: 10.54393/pjhs.v3i04.113
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Preoperative Anxiety Among Patients of Open-Heart Surgery at Cardiac Centres of Rawalpindi and Islamabad

Abstract: Anxiety is a complex emotional condition that is often described as a noxious internal disturbance that is accompanied by restlessness. Objectives: To determine the prevalence of preoperative anxiety and to find out main risk factors among patients waiting for open heart surgery. Methods: A cross-sectional study was carried out at cardiac centers of Rawalpindi. A total of 180 respondents who were admitted in hospital for open heart surgery were consecutively selected for the purpose of the study. APAIS and STA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
0
1
Order By: Relevance
“…8,14,23 In another study, it was reported that individuals between the ages of 20-46 have higher anxiety than those who are older. 24 The literature and the results of the current study have demonstrated inconsistent findings regarding the relationship between age and anxiety. This inconsistency may be attributed to differences in study methodology, inclusion of different age groups, variations in cultural characteristics, and examination of diverse patient populations.…”
Section: Discussioncontrasting
confidence: 53%
“…8,14,23 In another study, it was reported that individuals between the ages of 20-46 have higher anxiety than those who are older. 24 The literature and the results of the current study have demonstrated inconsistent findings regarding the relationship between age and anxiety. This inconsistency may be attributed to differences in study methodology, inclusion of different age groups, variations in cultural characteristics, and examination of diverse patient populations.…”
Section: Discussioncontrasting
confidence: 53%